New site Power Transmitter Analysis of 4G LTE FDD 1800 MHz Using Cell Splitting Method - Yuhanef, Afrizal -; Yusnita, Sri; Wafi, Rifki (Jurnal Edukasi Elektro, 2023)
The advancement of cellular telecommunications is growing day by day. Some theories, including 4G LTE FDD 1800 MHz, are becoming irrelevant to the current technology. The theory of power reduction by the cell splitting method is unsuitable for the actual condi-tions in the field. Theoretically, the cell splitting method is carried out on a new site with half of the main site's coverage, in which the transmitter power at the split site is reduced by 12 dB from the main site. This results in the power generated from the calculation be-ing small so that service coverage is limited. This study aimed to test the theory of trans-mitter power reduction in the cell splitting method (scenario 1) and compare it with other power reduction scenarios (Scenario 1: reduced by 15 dB, and Scenario 2: reduced by half from the main site power). The analysis is done by conducting simulations using Atoll RF Planning software. The study results revealed that in Scenario 3, the value of Key Perfor-mance Indicators is better than in other scenarios. The average throughput is 11045 kbps, the RSRP value is -108.58dBm, the range is 1.045 Km, and the average SINR is reduced to 8.52 dB. In addition, the data revealed that the coverage and signal quality of the site cell splitting is better when the transmitter power is 43 dBm (scenario 3). In conclusion, a site with higher transmitter power tends to have better signal strength, quality, and speed, as well as a wider coverage area. Reducing the transmitter cell splitting power will be more effective by reducing the new power site to half of the main site.